Go East, Young Man Imagining the American West as the Orient - Francaviglia, Richard (Utah State University Press, 2011)
"[Francaviglia's] book is of great value, particularly in its illuminating showcasing of the degree to which the American West was consistently compared to aspects of the Middle East, from desert sands and rock formations to camel caravans and mirages. These comparisons helped to establish the West as an exotic locale, markedly different from the Europe-focused eastern half of the country and having a fascination of its own." Journal of Folklore Research